A Study on the impact of FDI on economic growth in ASEAN - SON, Su Hyeon (KDI School, 2015)
This paper examines the impact of foreign direct investment (FDI) on economic growth of the Association of Southeast Asian Nations (ASEAN) countries, using the panel data of ASEAN 8 countries over the period of 2000-2012. Employing various social factors and macroeconomic indicators as independent variables for fixed effect model and random effect model, we find evidence for the positive impact of FDI on economic growth of the region in both estimations.
Thesis(Master) --KDI School:Master of Development Policy,2015